Geodetic evidence for post-seismic deformations following the 2014 North Aegean Mw 6.9 earthquake - Gianniou, Michail; Argyrakis, Panagiotis; Prasinou, Tatiani (Geodesy and Cartography, 2023)
The 2014 North Aegean Sea earthquake was a strong (Mw 6.9) event that caused significant crustal deformations. In the present study we investigate the long-term impact of the earthquake on the kinematics of the North Aegean Trough (NAT). For this purpose, we analyzed GPS observations collected from May 2010 to April 2022 at five permanent GPS reference stations. Two of these stations are located close to the epicenter(s) on the Islands of Lemnos and Samothrace. We processed the data using the Precise Point Positioning (PPP) technique. The analysis of the obtained coordinate time-series revealed a post-seismic deformation (PSD) period lasting for more than two years leading to cumulative 2D post-seismic displacement of 22 mm and 27 mm for Samothrace and Lemnos, respectively. The magnitudes of these post-seismic slip vectors correspond to 23% and 49% of the co-seismic vectors at Samothrace and Lemnos, respectively. The long-term analysis showed that after the end of the PSD period the stations are characterized by stable velocities that are noticeably different compared to the velocities prior to the event. We observed a change in the velocity in the order of 2 mm/yr for both Samothrace and Lemnos. It is the first time that PSD and velocity changes have been reported for the 2014 North Aegean Sea earthquake shedding light on the characteristics and the impact of this important earthquake on the kinematics of NAT.